2006
DOI: 10.1530/eje.1.02221
|View full text |Cite
|
Sign up to set email alerts
|

Plasma dipeptidyl peptidase-IV activity in patients with type-2 diabetes mellitus correlates positively with HbAlc levels, but is not acutely affected by food intake

Abstract: Objective: Glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide are incretin hormones, secreted in response to meal ingestion. The incretin hormones stimulate insulin secretion and are essential for the maintenance of normal plasma glucose concentrations. Both incretin hormones are metabolized quickly by the enzyme dipeptidyl peptidase-IV (DPP-IV). It is well known that type-2 diabetic patients have an impaired incretin effect. Therefore, the aim of the present study was to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
155
6
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(175 citation statements)
references
References 35 publications
13
155
6
1
Order By: Relevance
“…Hence, the increased DDP-IV activity in the patients studied by Vilsbøll et al should result in lower p-active GLP-1 levels relative to those in our patients, but the p-active GLP-1 levels were actually higher than those seen in our patients [2]. Furthermore, the p-active GLP-1 levels may increase when patients have hypoglycemia, as in patients with type 2 diabetes [9], but no patients with hypoglycemia participated in either study. Therefore, glycemic state may be not directly related to these differences between the studies.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…Hence, the increased DDP-IV activity in the patients studied by Vilsbøll et al should result in lower p-active GLP-1 levels relative to those in our patients, but the p-active GLP-1 levels were actually higher than those seen in our patients [2]. Furthermore, the p-active GLP-1 levels may increase when patients have hypoglycemia, as in patients with type 2 diabetes [9], but no patients with hypoglycemia participated in either study. Therefore, glycemic state may be not directly related to these differences between the studies.…”
Section: Resultscontrasting
confidence: 53%
“…Hyperglycemia evaluated by HbA1c levels increases DPP-IV activity in patients with type 1 diabetes [8]. Moreover, serum DPP-IV activity is positively correlated to fasting plasma glucose and HbAlc levels in patients with type 2 diabetes [9]. Hence, the increased DDP-IV activity in the patients studied by Vilsbøll et al should result in lower p-active GLP-1 levels relative to those in our patients, but the p-active GLP-1 levels were actually higher than those seen in our patients [2].…”
Section: Resultsmentioning
confidence: 98%
“…Pala et al reported that oral glucose loading did not induce DPP4 activation in normal, impaired glucose tolerance, or type 2 diabetes subjects [21]. In addition, Ryskjaer et al reported that plasma DPP4 activity is not altered following meal ingestion or acute changes in the plasma glucose level [10]. Taking these findings together, we assume that DPP4 biosynthesis is correlated with longterm exposure to a high glucose concentration.…”
Section: Dpp4 Enzyme Assaymentioning
confidence: 55%
“…1). The correlations between DPP4 activity and BMI (r = 0.24, p = 0.0017) and total cholesterol (r = 0.27, p = 0.0006) remained significant after adjusting for age and sex (Table 3), but not found to increase [9,10] and decrease [11][12][13] in patients with type-2 diabetes. Moreover, it has been reported that the degree of plasma DPP4 activity was significantly higher in obese subjects than in lean subjects [14,15]; however, the DPP4 hyperactivity in obese individuals did not seem to be affected by their degree of overweightedness [14].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation